SISTEM PENUNJANG KEPUTUSAN KRITERIA BEASISWA MENGGUNAKAN RULE BASED DAN FORWARD CHAINING - Nurul Azizaturrizqiyah; Munawarah -; Tholib Hariono (KH. A. Wahab Hasbullah University, 2016)
It is known in the selection of the scholarship will certainly experience difficulties because of the many criteria for scholarship applicants and the number of criteria used to determine the grantee's decision as expected. Therefore the need for a system of decision-makers to take into account all the criteria that support decision making by using rule-based and forward chaining, because the rule-based and forward chaining will implement a counting system for certain that the admin just entering data and will gain value in accordance with the criteria.In this study, the author tries to analyze the main points of the discussion and the results are intended to develop information systems that can be used in AMIK Jombang. System decision makers have preferred to build a decision matrix, decision making matrix is normalized, weighted normalized decision making matrix, determine the positive and negative ideal solution, calculate separation, calculate the relative proximity to the positive ideal solution, rank the alternatives. The final result of the data sorting recipients.Â Keywords: scholarships, rule based dan forward chaining